High-Level Extracellular Expression of a New β-N-Acetylglucosaminidase in Escherichia coli for Producing GlcNAc - Li, Congna; Jiang, Shun; Du, Chao; Lu, Zhenghui; He, Nisha; Zhou, Yuling; Jiang S, Sijing; Zhang G, Guimin (Frontiers in Microbiology, 2021)
N-acetyl-β-D glucosamine (GlcNAc) is wildly used in cosmetics, nutraceuticals and pharmaceuticals. The traditional chemical process for GlcNAc production from chitin causes serious acidic pollution. Therefore, the enzymatic hydrolysis becomes a great promising and alternative strategy to produce GlcNAc. β-N-acetylglucosaminidase (NAGase) can hydrolyze chitin to produce GlcNAc. Here, a GH3 family NAGase encoding gene BlNagZ from Bacillus licheniformis was expressed extracellularly in Escherichia coli guided by signal peptide PelB. The recombinant BlNagZ presented the best activity at 60°C and pH 5.5 with a high specific activity of 13.05 U/mg. The BlNagZ activity in the fermentation supernatant can reach 13.62 U/mL after optimizing the culture conditions, which is 4.25 times higher than optimization before. Finally, combining BlNagZ with chitinase ChiA we identified before, chitin conversion efficiency to GlcNAc can reach 89.2% within 3.5 h. In all, this study provided not only a high active NAGase, and a secreted expression strategy to reduce the cost of production, which is conducive to the industrial application.